2013
DOI: 10.1089/aid.2013.0135
|View full text |Cite
|
Sign up to set email alerts
|

Subtype B Was the Dominant Strain Among HIV Type 1 Infections Except for the Population of Men Who Have Sex with Men in Harbin City, China

Abstract: We sought to identify the prevalent subtypes and study the genetic variation of HIV-1 circulating in HIV infections in Harbin City, China. Forty-seven samples from the env V3-V4 region were successfully sequenced and analyzed, which involved thirty-one men who have sex with men (MSM), eight heterosexuals, seven former plasma donors (FPD)/blood transfusion recipients (BT), and one injection drug user (IDU). In all, 46.8% of CRF01_AE, 40.4% of subtype B, and 12.8% of CRF07_BC were identified. CRF01_AE (64.5%) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…Similarly with Choi's study [5], the present study found that the younger age of sexual debut with men was associated with larger size of social networks ( r = −0.15) and larger social networks were associated with the use of HIV prevention services. However, our findings differ with another report that suggests MSM sexual debut predicted more frequently change of sex partners and other risk behaviors [36].…”
Section: Discussionsupporting
confidence: 87%
“…Similarly with Choi's study [5], the present study found that the younger age of sexual debut with men was associated with larger size of social networks ( r = −0.15) and larger social networks were associated with the use of HIV prevention services. However, our findings differ with another report that suggests MSM sexual debut predicted more frequently change of sex partners and other risk behaviors [36].…”
Section: Discussionsupporting
confidence: 87%
“…These data came from the following references: Wang et al, ; Liu et al, ; Li et al, ; Shao et al, .…”
Section: Resultsmentioning
confidence: 99%
“…Third, because of the absence of CRF01_AE from all regions of the country, the epidemiologic characteristics of the CRF01_AE prevalence may not be intact nationwide. In addition, the sequences obtained successfully were disproportionate with the actual number of annual reported cases in Harbin during the a These data came from the following references: Wang et al, 2007;Liu et al, 2009;Li et al, 2012;Shao et al, 2013. b Present study included only one sequence from the blood sample collected in 2009. retrospective period. The results obtained from the present study mainly reflect the status of the HIV epidemic between 2011 and 2013.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Importantly, however, migrants in Shenzhen had significantly different HIV-1 subtype distributions from MSM still living in their home regions (p < 0.01) 12 25 26 27 28 29 30 31 32 33 ( Fig. 2 ).…”
Section: Discussionmentioning
confidence: 97%